(untitled) - Silverman, Harold M. (Toronto, 1993)
Detailed descriptions of vitamins, minerals, trace elements, and electrolytes, including daily requirements, dosages, therapeutic uses, and more.
Keywords: Vitamins in human nutrition,Vitamin trong dinh dưỡng con người; Handbooks, manuals, ect,Sổ tay, sách hướng dẫn, vv